Pogram in Gujarat: Hindu nationalism and anti-muslim violence in India - Ghassem-Fachandi, Parvis (New Jersey Princeton University press, 2012)
In 2002, after an altercation between Muslim vendors and Hindu travelers at a railway station in the Indian state of Gujarat, fifty-nine Hindu pilgrims were burned to death. The ruling nationalist Bharatiya Janata Party blamed Gujarat's entire Muslim minority for the tragedy and incited fellow Hindus to exact revenge.
Keywords: Pogroms India Gujarat; Muslims violence against India Gujarat; Ethnic conflict India Gujarat